Douglass North : hétérodoxie néo-institutionnelle versus néolibéralisme ? - Benoît Prévost (Revue de la Régulation)
Douglass North rejects the extension of neoclassical analysis to the explanation of development phenomena. He demonstrates that efficient institutions could not been rationaly designed on the basis of economic theory. D. North then initiates a kind of new institutional heterodoxy that could undermine the institutional adjustment strategies supported by the Bretton Woods Institutions in the Developing Countries.